Systematic Review: Gastrointestinal infection and incident inflammatory bowel disease - Axelrad, Jordan E. (Aliment Pharmacol Ther, 2020)
BACKGROUND: The initiating events of chronic gastrointestinal (GI) inflammation in Crohn’s disease (CD) and ulcerative colitis (UC) are not well-defined, but GI infections are implicated. AIMS: We conducted a systematic review with the primary aim of defining the role of GI infections in risk of incident inflammatory bowel disease (IBD), and secondarily, of synthesizing the current body of relevant translational data to provide biological context for associations between GI infections and IBD risk. METHODS: We systematically reviewed electronic databases through July 2019. Clinical studies that provided risk estimates of the association between GI infections and incident IBD were included. Inclusion criteria were broader for translational studies aiming to define mechanisms of GI infections and predisposition to or protection from IBD. RESULTS: Of the studies identified, 63 met full inclusion criteria. Among studies of clinical gastroenteritis, bacteria—specifically, Salmonella species, Campylobacter species, and Clostridioides difficile—demonstrated consistent positive associations with risk of incident IBD. Of viruses, norovirus was associated with increased risk of incident CD. Regarding inverse associations with incident IBD, Helicobacter pylori and helminth infections were associated with a generally consistent reduced risk of IBD. Based on a qualitative analysis of the translational data, putative mechanisms involve multiple microbial and immunologic pathways. CONCLUSIONS: Based on this systematic review, certain enteric pathogens are associated with an increased risk of incident IBD, while others are potentially protective. Prospective studies are required to clarify the clinical implications of these enteric pathogens on the risk and course of IBD, not to mention possible therapeutic or preventative benefit.